PROS1 (Cys228Tyr) missense mutation associated with mesenteric and pulmonary venous thromboembolism during the COVID-19 pandemic: a case report - Jingyi Huang; Jingyi Huang; Yunjian Zhang; Haixu Yu; Wei Liu (Frontiers in Cardiovascular Medicine)
BackgroundVenous thromboembolism (VTE) is influenced by both genetic and acquired risk factors, with protein S (PS) deficiency recognized as a well-established inherited thrombophilia. Introduction: We report the case of a 32-year-old male patient presenting with mesenteric venous thrombosis and pulmonary embolism caused by a missense mutation in PROS1 during the COVID-19 pandemic.MethodsThe patient presented with pleuritic chest pain and low-grade fever 15 days after a confirmed COVID-19 infection. Despite initial treatment with glucocorticoids and a macrolide antibiotic, his symptoms worsened and his D-dimer level increased. CT pulmonary angiography confirmed an acute pulmonary embolism.ResultsClinical history revealed a prior episode of mesenteric vein thrombosis and multiple acquired risk factors, including obesity, sedentariness, COVID-19 infection, glucocorticoid treatment, inflammatory response (elevated CRP and serum ferritin levels), and metabolic abnormalities (non-alcoholic fatty liver disease, hyperuricemia, and hyperlipidemia). Laboratory testing showed decreased PS activity, and genetic sequencing identified a heterozygous missense mutation in PROS1, c.683G>A (p.Cys228Tyr). The patient was treated with low-molecular-weight heparin (LMWH) followed by rivaroxaban. Discussion: No recurrence of VTE of bleeding events was observed during a one-year follow-up, suggesting effective management of thrombosis in the context of both inherited and acquired prothrombotic conditions.